Astenopia relacionada a los niveles de iluminación en los puestos de servicio de los miembros de los ministerios de la Iglesia Internacional Escape, Guayaquil junio - septiembre 2024. - Izquierdo Campuzano, Milena Michelle (2024)
The research project entitled Asthenopia related to lighting levels in service positions of members of the ministries of the ESCAPE International Church, Guayaquil, June-September 2024, has as its general objective to analyze the relationship between lighting levels and asthenopia in service positions of members of the ministries of the ESCAPE International Church, in which the research focuses on asthenopia as one of the main visual problems that affects workers according to the WHO, due to inadequate lighting in work areas. For this project, descriptive research was used, and an online survey was applied to the sample, which seeks to identify the frequency of asthenopia in members of the church's ministries. Likewise, a luxometer was used, an instrument used to measure lighting levels, to collect data for this research. The results of the luxometer medication indicate that there are low levels of lighting in the service posts, as well as the results of the survey, the most relevant question was 2, which indicates that most of the lighting in the service posts is artificial lighting, which stands out with 87.5%, which is why the members present various symptoms, then it was concluded that the service posts of the members of the Church ministries need an improvement in their lighting.